THE INFLUENCE OF ISLAMIC BOARDING SCHOOL ENVIRONMENT AND TA’LIM MUTA’ALIM ON MORALS TOWARDS TEACHERS: THE ROLE OF SELF-AWARENESS - Nurhidayah, Litha Kurnia; Choiri, Moh Miftachul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study investigates the influence of the Islamic boarding school (pesantren) environment and Ta'lim Muta'alim studies on students' moral behavior towards teachers, with a focus on the mediating role of self-awareness. Grounded in the principles of Islamic education, the study addresses the critical issue of declining moral respect towards teachers in educational institutions. Using a quantitative research design, data were collected from 110 students of Jannaturroichan Islamic Boarding School in Jombang. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the relationships between variables. The results revealed that both the pesantren environment and Ta'lim Muta'alim studies significantly enhance students' moral conduct towards teachers, and self-awareness acts as a crucial mediator in strengthening this relationship. The findings highlight the novelty of integrating self-awareness as a core component in Islamic moral education to foster deeper respect for teachers. Based on these results, it is recommended that pesantren incorporate structured self-awareness training programs to cultivate positive student-teacher interactions and reinforce moral values within the educational framework of Islamic boarding schools.